FISCAL EFFECTIVENESS ASSESSMENT OF THE BUDGET-GENERATING TAXES IN UKRAINE (World of finance, 2021)
Introduction. A significant share of tax revenues in the revenue part structure of the Consolidated budget of Ukraine forms the grounds for assessing the economic efficiency of established taxes in order to make managerial decisions in the budget and tax management field at the macro level. Therefore, it is important to analyse the fiscal effectiveness indicators of taxes that form the tax revenues majority to the budgets of Ukraine, as well as to identify socio-economic factors that affect the size of such revenues.The purpose of the article is to analyse the fiscal effectiveness indicators of budget-generating taxes, to perform a correlation analysis of the tax revenues dependence on macroeconomic indicators and substantiate ways to increase the tax revenues sources to budgets of different levels.Results. The scientists’ approaches to the definition of the essence of the category “fiscal efficiency” were considered as well as was monitored the volume and structure of tax revenues to the Consolidated budget of Ukraine for 2015–2020. The factors of fiscal effectiveness were investigated and its assessment was carried out on the basis of data on the revenues of value added tax, personal income tax, excise tax and corporate income tax to the Consolidated budget using indicators of the fiscal significance of the tax in the budget, the fiscal significance of the tax in the state GDP and the ratio of the predicted and actual indicators of tax revenues. It was performed a correlation analysis of budget-forming taxes with macroeconomic indicators, as a result of which close relationship has been determined between the number of introduced types of innovative products and the volume of value-added tax revenues of goods (work and services) produced in Ukraine; the volume of revenues from corporate income tax and capital investments made by business entities, as well as between the volume of revenues from excise tax and the number of unemployed population in Ukraine. Based on the results of the investigation, there were proposed and substantiated the ways of tax reforms and directions of government measures to increase tax revenues.